The role of undergraduate research in physics education - López Gallardo, Jorge Alberto (Cultura Científica y Tecnológica, 2023)
Research experiences can benefit undergraduate students by providing hands-on experience in research, helping them develop critical thinking, problem-solving and analytical skills. Also, it helps them in establishing professional networking, career exploration, and demonstrable experience for future employers. In this article, the different types of undergraduate research experience that exist are explored. The article annotates several investigations of the benefits of undergraduate research experiences, including two that relate research experiences to the continuation into graduate school. This work also presents statistical data from the author’s university of affiliation, to conclude that undergraduate research is the strongest motivator there is for students to continue with graduate studies.